2009
DOI: 10.1080/02770900902818371
|View full text |Cite
|
Sign up to set email alerts
|

What Affects Asthma Medicine Use in Children? Australian Asthma Educator Perspectives

Abstract: The global burden of childhood asthma is significant. Health care systems are faced with increasing financial costs, while children with asthma and their caretakers are faced with poorer physical health, emotional health, and quality of life. Despite the availability of effective treatment, the quality use of asthma medicines in children remains suboptimal. An investigation was conducted to explore issues related to children's asthma medicine usage from the perspective of the health care professional. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…Parental fear of ICS ("steroid phobia") is reported extensively as a major barrier to the use of and adherence to asthma medications ( 45,48,(64)(65)(66)(67)(68). Interestingly, an emerging trend is the high use of CAM.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Parental fear of ICS ("steroid phobia") is reported extensively as a major barrier to the use of and adherence to asthma medications ( 45,48,(64)(65)(66)(67)(68). Interestingly, an emerging trend is the high use of CAM.…”
Section: Discussionmentioning
confidence: 98%
“…One of the key themes to emerge from our review was that parental knowledge, attitudes, beliefs, socioeconomic characteristics, and family interaction patterns can all contribute to inappropriate use of medications (29,45,62,63). Parental fear of ICS ("steroid phobia") is reported extensively as a major barrier to the use of and adherence to asthma medications ( 45,48,(64)(65)(66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Grover and colleagues identified a key barrier to the management of paediatric asthma in primary care to be the inability of health care professionals to effectively communicate with the patient/ carer [5,9]. In further support of this point, 38 % of Australian parents feel they do not have enough information about their child's asthma [8].…”
Section: Introductionmentioning
confidence: 88%